Nothing but the truth [videorecording (DVD)] - Lurie, Rod, 1962-; Beckinsale, Kate; Dillon, Matt; Bassett, Angela (Sony Pictures Home Entertainment, 2009)
A volatile story about a Washington, D.C. political reporter who writes an explosive story about a government scandal in which she reveals the name of a covert CIA agent. Unexpectedly finding herself behind bars, she struggles to maintain her principles and relationship with her family when she refuses to divulge her source. Inspired by true events.